Approaches to diagnosis and detection of cassava brown streak virus (Potiviridae: Ipomovirus) in fieldgrown cassava crop - Rwegasira, G.M.; Rey, M.E.C.; Nawabu, H. (2011)
Cassava brown streak disease (CBSD) has been a problem in the East African coastal cassava growing areas for more than 70 years. The disease is caused by successful infection with Cassava Brown Streak Virus (CBSV) (Family, Potyviridae: Genus, Ipomovirus). Diagnosis of CBSD has for long been primarily leaf symptoms-based. This is unreliable due to the irregular pattern and variability of the disease phenotype in roots and leaves. The suitable method to undertake reliable field diagnostic survey and derive acceptable analysis of the disease situation has never been standardized. Zigzag and diagonal approaches for disease assessment have been used successfully on other diseases infecting cassava such as Cassava mosaic disease but neither of them has ever been tested and proven suitable for CBSD assessment. In addition, the suitable sample for successful molecular detection of the causal virus has never been optimised. The number of samples to be collected from large plant stands which would be a true representation of the population has never been determined. The effect of sample bulking on possible detection or non detection of infection particularly when un-infected samples are combined with infected ones is not known. In this study, the comparative efficiencies of diagonal and zigzag approaches to CBSD field diagnosis were tested through surveys conducted in 20 randomly selected farmers’ fields in major cassava growing areas of the Coastal and Lake Zones in Tanzania. Using molecular diagnostic techniques, the plant parts which are suitable for Cassava brown streak virus (CBSV) detection were determined. Sample bulking was tested for rationalized laboratory detection of CBSV over large cassava stands. The study revealed that CBSD incidences and severities obtained using either diagonal or zigzag approach did not differ significantly. Suitable parts for CBSV detection were identified to be flowers, fruits, apical buds, young tender leaves, newly-opened leaves, youngest symptomatic leaves, the tender top-green portion of the stem and non-necrotic storage root tissues. CBSV was not detected in seeds. In bulked leaf samples, CBSV was detected from ratios of 1:1 up to 1:19 of CBSVinfected to CBSV-free tissues in cultivar Albert. It was concluded that either zigzag or diagonal can be used for CBSD field diagnosis. A choice of the suitable sample is of absolute necessity, and bulking of many samples for collective CBSV detection over a large crop stand is effective.